The export barriers of premium alcohol companies from Finland - Aho, Aino (fi=Turun yliopisto|en=University of Turku|, 2018)
In recent years, the industry of premium alcohol has boomed in Finland and researchers as well as authorities have recognized the potential of premium alcohol products internationally. Today, the alcohol industry has become an important driver of economic growth for Finland. However, to further foster growth of the industry, it is important to find out which are the most important export barriers of these companies and how to overcome their export barriers. Hence, the aim of this study is to explore this phenomenon and point out the internal and external export barriers of Finnish premium alcohol companies and proposing ways to overcome the barriers. First a pilot interview was held together with Food from Finland industry experts. Then three case companies where interviewed, and each of the companies represents a firm of different size and experience within the premium alcohol industry in Finland. The companies were either active exporters, export-oriented or something in between. A semi-structured method of conducting the interviews was chosen for the study and the interviewed persons were either export directors or founder-owners of the companies. When assessing the findings of the interviews, the researcher benefitted from the industry experts’ discussion and earlier research results. The industry of premium alcohol in Finland seems to be represented by a “younger generation”, who seem to be natural born internationals. Yet, the internal barriers of exports affect especially when initiating exports, while the impact of some external export barriers shows during the export process itself. The companies face more internal barriers, partly due to the limited experience of the export staff in these companies. Especially because more and more young producers are in charge of exports, should the premium alcohol people learn from each other’s mistakes and do their homework. The export strategy should be well structured. A finding of the study is that companies might not have prioritized exports which is why processes are not conducted smoothly. Similar strong targeting of the domestic and foreign market can cannibalize the business and be a burden to the company. The competition to win consumers and customers on your side is tough. To overcome export barriers, one should invest into storytelling, marketing and obtaining international experience, which leads to better structured export strategies. By building a hollow brand and preparing a coherent export strategy, the companies can enable better export success. By learning from others, companies can speed up overcoming and avoiding barriers. Due to the limitation of studying only Finnish companies in the industry, the observations are not to be understood as common outcomes for all companies operating within the alcohol industry or being of Finnish origin. However, in this context some findings are observed. When comparing the findings of this study to earlier researches on export barriers, we can find similarities and surprising findings. The younger and smaller companies face more internal barriers in general than their larger counterparts who manage to structure their processes. Better networking together with domestic competitors could enable sharing knowledge.